POLYMORPHISM OF SOME SPECIES FROM THE TRIBE VICIEAE BRONN (FABACEAE LINDL.) ACCORDING TO THE DATA OF MORPHOLOGICAL AND MOLECULAR GENETIC ANALYSIS - M. O. Burlyaeva; D. A. Krivenko; E. M. Machs; A. S. Sabitov (Труды по прикладной ботанике, генетике и селекции)
Morphological, karyological and molecular genetic analyses of the accessions of Vicia unijuga A. Br. s. 1 (V. unijuga A. Br., V. ohwiana Hosok.) from the tribe Vicieae Bronn. have been performed. Samples were collected during expeditions in the Russian Far East, Siberia and China. The results of factor and discriminant analysis revealed as important morphological characters for the classification of inter- and intraspecific diversity: peduncle length, leaf length, stipule shape, bean length, and the number of internodes on the main stem. The cytotypes 2n = 12, 2n = 24 at V. unijuga and V. ohwiana Hosok. were found to occur almost over the entire territory of their areas of distribution. 2n = 12 is not species-specific characteristics for V. ohwiana. The ITS, SSR and ISSR marker analyses revealed a significant taxonomic proximity of V. unijuga and V. ohwiana with the species V. baicalensis (Turcz.) B. Fedtsch., V. ramuliflora (Maxim.) Ohwi and V. venosa (Willd. ex Link) Maksim. The complex species V. unijuga s. 1 is a genetically heterogeneous group. Some populations localized on the islands and the coast of the Sea of Japan need to be classified into independent taxa of a higher rank.